Community Perception of The Causes of The Tsunami Disaster In Pandeglang Regency and Palu City, Indonesia - Kurniadi, Anwar (Technium Social Sciences Journal, 2022)
The tsunami disaster resulted in many casualties, facilities and infrastructure, property, and environmental damage in both Pandeglang Regency and Palu City. As a result of this suffering, it is likely that this will become the basis for informants to express their perceptions about the causes of the tsunami disaster. A good understanding of the public’s perception of the causes of the tsunami disaster will make it easier to understand the relationship between nature, humans, society, and capacities as well as how to overcome adverse impacts before the tsunami disaster strikes. This study aims to analyze community perceptions about the causes of the tsunami disaster in Pandeglang Regency and Palu Municipality. The research method uses a qualitative phenomenological design. The data collection method used in-depth interviews, direct field observations, and documentation to analyze what was revealed by 10 informants based on their knowledge and experience when affected by the tsunami disaster. The results showed that the causes of the tsunami disaster were the wrath of God, fate or fatalism factors, and natural factors. The fate factor or fatalism is a view that agrees to give up before fighting. This can disrupt the tsunami disaster management process using the new Paradigm. The new paradigm is to prioritize efforts to reduce the risk of tsunami disasters by making people and local governments aware in the form of disaster prevention measures. The action is to conduct a disaster risk assessment and make a contingency plan before the arrival of the tsunami disaster.